2001
DOI: 10.1890/1051-0761(2001)011[0530:eofrof]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flow Regime on Fish Assemblages in a Regulated California Stream

Abstract: The fishes in Lower Putah Creek, a regulated stream in the Central Valley of California, were sampled over a 5-yr period, 1994-1998. Distinct fish assemblages were observed in the lower 37 km of stream using two-way indicator species analysis (TWIN-SPAN) and canonical correspondence analysis (CCA). The assemblages segregated in an upstream-to-downstream manner. Distinct differences were found between assemblages of native and nonnative fishes and their association with environmental variables and habitat use. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(156 citation statements)
references
References 26 publications
6
148
1
1
Order By: Relevance
“…Some of these annual differences in fish community composition appear to be driven by the interannual variability of freshwater inflow into the Delta, a pattern reflected in the second NMDS axis (Fig 3). This result is not surprising given that numerous studies have demonstrated a strong relationship between fish community and hydrologic variability in California [72,73,74,75]. Yet, the largest differentiation between years, as captured by the first NMDS axis, seems to follow a pattern of continuous change over time.…”
Section: Discussionmentioning
confidence: 66%
“…Some of these annual differences in fish community composition appear to be driven by the interannual variability of freshwater inflow into the Delta, a pattern reflected in the second NMDS axis (Fig 3). This result is not surprising given that numerous studies have demonstrated a strong relationship between fish community and hydrologic variability in California [72,73,74,75]. Yet, the largest differentiation between years, as captured by the first NMDS axis, seems to follow a pattern of continuous change over time.…”
Section: Discussionmentioning
confidence: 66%
“…Diversions and groundwater pumping have reduced total and base streamflows, thus increasing riparian water stress (McKay and King, 2006;Caskey et al, 2014), while dam operations have increased low flows, reduced flood magnitude and frequency, altered flood timing, and impeded sediment movement, thus reducing fluvial disturbance and hindering riparian ecosystem dynamics (Graf, 2006;Poff and Zimmerman, 2010;Grill et al, 2015). On rivers with reduced low flows, adequate low flows may be restored by purchasing water rights, setting flow targets during dam relicensing, or increasing water-use efficiency to reduce water demand (Marchetti and Moyle, 2001;Poff et al, 2007;Acreman et al, 2014). On rivers with reduced low flows, adequate low flows may be restored by purchasing water rights, setting flow targets during dam relicensing, or increasing water-use efficiency to reduce water demand (Marchetti and Moyle, 2001;Poff et al, 2007;Acreman et al, 2014).…”
Section: Water Managementmentioning
confidence: 99%
“…Aspects of the flow regime are known to be linked to critical aspects of the life history of fishes (Welcomme, 1985;Junk et al, 1989;Humphries et al, 1999;Poff et al, 2003;Lytle and Poff, 2004), and therefore, providing more natural flow regimes in regulated rivers is seen as one potential restoration measures (Marchetti and Moyle, 2001;Arthington et al, 2006). However, examples of its use are limited and those that are available have had varying successes.…”
Section: The Role Of Flooding In Spawning and Recruitment Of Native Fishmentioning
confidence: 99%